Smart Monitoring System of DC to DC Converter for Photovoltaic Application - Jameel Kadhim Abed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper presents a new smart monitoring system designed based on dc to dc converter for photovoltaic application. This system design according two parts to monitor input-output voltages and currents for dc/dc converter, (a) control system: the control system using Arduino NANO as microcontroller to read the measuring voltage and current values from sensor circuits of voltage and current. The measuring data send by Bluetooth HC-05 to end user (monitor system). Bluetooth as wireless communication between the control system and monitoring system (end users). (b) monitoring system: The monitoring system application program as a new application designed to monitor the received data from control system from safety distance (around 10m). the application program designed by the open source AppyBuilder software. The AppyBuilder is an open source software for easily building Android smartphone application. The advantages of the final circuit can be used to monitor step-up or step-down topologies, low-cost, and high-efficiency performance.